LEGAL PROTECTION OF DATA SECURITY OF E-COMMERCE APPLICATIONS DURING THE COVID-19 PANDEMIC - Fitriyani Dewi Siregar; Muhammad Yusrizal Adi Syaputra (NOMOI Law Review, 2021)
The rapid progress in the field of information technology has contributed greatly to the development of the world of information and electronic transactions. The security of consumer personal data that enters e-commerce data should be a guarantee given by the company to its consumers. This study aims to find out the legal protection for data/information security of e-commerce application users during a pandemic. This study uses normative legal research with analytical descriptive methods to explain, describe, and correlate legal regulations and theories with the problems that occur. Data analysis was carried out qualitatively. The results of the study indicate that the electronic system operator must ensure the availability of service level agreements, the availability of information security agreements for the information technology services used; and security of information and means of internal communication held. Then, the operator of the electronic system must ensure that each component and the integration of the entire electronic system operates properly. Especially in the era of the covid-19 pandemic, it is appropriate that the regulation of personal data protection can be immediately upgraded to the level of the law.Keywords: Protection; Security; Personal Data;E-Commerce.